PENGARUH INSENTIF PAJAK, TARIF PAJAK, KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI USAHAWAN SELAMA MASA PANDEMI COVID-19 DI TAMBORA - Selinda Agustine; Leonard Pangaribuan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Tax revenue is one of the sources of funds that can be used to finance national development. The Covid-19 pandemic has had an impact on decreasing consumption levels, weakening investment, and declining commodity prices which have caused taxpayer compliance not to be maximized. This study aims to examine the effect of tax incentives, tax rates, taxpayer awareness and tax sanctions on individual entrepreneur taxpayer compliance during the Covid-19 pandemic in Tambora. This research is a quantitative research and the data obtained is the result of distributing questionnaires in January 2022. Then it will be tested with descriptive analysis, classical assumption test, multiple linear regression and hypothesis testing using IBM SPSS Ver.25. The results of the t test in this study obtained the value of sig. 0.297 for the tax incentive variable (X₁), the value of sig. 0.317 for the variable tax rate (X₂), the value of sig. 0.011 for the taxpayer awareness variable (X₃) and sig. 0.0005 for the tax penalty variable (X₄). The conclusion obtained from the results of this study is that there is insufficient evidence that tax incentives and tax rates have a positive effect on individual entrepreneur taxpayer compliance during the Covid-19 pandemic, while there is sufficient evidence that taxpayer awareness and tax sanctions have a positive effect on individual entrepreneur taxpayer compliance during the Covid-19 pandemic.